Determination of the Atterberg limits using a Fall cone device on low plasticity silty sands (Rudarsko-geološko-naftni zbornik, 2023)
The Fall cone liquid limit testing procedure for low plasticity soil mixtures with sand, including the sample preparation procedure and the implementation of Fall cone plastic limit determination suggestions are covered within this research. A Fall cone apparatus was used in order to determine the liquid and plastic limits of soil types, for which the Casagrande cup and thread rolling methods proved inapplicable. Several issues are addressed concerning standardized sample mixture preparation and cup filling procedures for liquid limit testing, as well as the applicability of single measurements per moisture content and the effect of curing time on data gain quality. Both liquid and plastic limit testing results show a solid and expected linear trend of high precision. Liquid limit testing results correlate well with the existing data which suggests the Fall cone method as a unique liquid limit testing method for mixtures of low plasticity clays with sand. Plastic limit determination methods results show a deviation from values obtained with the classical Casagrande’s thread rolling method which could be caused by the bias in the tested soil type or apparatus. Test results are presented numerically and graphically and discussed with a focus on the given method applicability for determining Atterberg limits of low plasticity soil mixtures with sand.